NANOSTRUCTURAL PROCESSES OF MELTING AND CRYSTALLIZATION OF CAST IRON - V. Stetsenko (Литьë и металлургия, 2015)
It is shown that melt of cast iron of the eutectic structure consist of austenite nanocrystals, graphite, acementite and atoms of iron. Processof melting and crystallization of cast iron is difficult physical and chemical nanoprocess. Thermodynamic it is established that this process generally is defined by intensity of diffusion of atoms of carbon and speed of hardening of cast iron.